CD4+T and CD8+T Cells in Uterus Exhibit Both Selective Dysfunction and Residency Signatures - Shuangpeng Kang; Shuiping Jin; Xueying Mao; BinSheng He; Changyou Wu (Journal of Immunology Research)
Unlike T cells in other tissues, uterine T cells must balance strong immune defense against pathogens with tolerance to semiallogeneic fetus. Our previous study fully elucidated the characteristics of γδT cells in nonpregnant uterus and the mechanism modulated by estrogen. However, comprehensive knowledge of the immunological properties of αβT (including CD4+T cells and CD8+T) cells in nonpregnancy uterus has not been acquired. In this study, we fully compared the immunological properties of αβT cells between uterus and blood using mouse and human sample. It showed that most of CD4+T cells and CD8+T cells in murine uterus and human endometrium were tissue resident memory T cells which highly expressed tissue residence markers CD69 and/or CD103. In addition, both CD4+T cells and CD8+T cells in uterus highly expressed inhibitory molecular PD-1 and cytokine IFN-γ. Uterine CD4+T cells highly expressed IL-17 and modulated by transcription factor pSTAT3. Moreover, we compared the similarities and differences between human and murine uterine T cell phenotype. Together, uterine CD4+T cells and CD8+ cells exhibited a unique mixed signature of T cell dysfunction, activation, and effector function which enabled them to balance strong immune defense against pathogens with tolerance to fetus. Our study fully elucidated the unique immunologic properties of uterine CD4+T and CD8+T cells and provided a base for further investigation of functions.